Arctic – Atlantic Exchange of the Dissolved Micronutrients Iron, Manganese, Cobalt, Nickel, Copper and Zinc With a Focus on Fram Strait. Issue 5 (16th May 2022) - Krisch, Stephan; Hopwood, Mark J.; Roig, Stéphane; Gerringa, Loes J. A.; Middag, Rob; Rutgers van der Loeff, Michiel M.; Petrova, Mariia V.; Lodeiro, Pablo; Colombo, Manuel; Cullen, Jay T.; Jackson, Sarah L.; Heimbürger‐Boavida, Lars‐Eric; et al.
Abstract: The Arctic Ocean is considered a source of micronutrients to the Nordic Seas and the North Atlantic Ocean through the gateway of Fram Strait (FS). However, there is a paucity of trace element data from across the Arctic Ocean gateways, and so it remains unclear how Arctic and North Atlantic exchange shapes micronutrient availability in the two ocean basins. In 2015 and 2016, GEOTRACES cruises sampled the Barents Sea Opening (GN04, 2015) and FS (GN05, 2016) for dissolved iron (dFe), manganese (dMn), cobalt (dCo), nickel (dNi), copper (dCu) and zinc (dZn). Together with the most recent synopsis of Arctic‐Atlantic volume fluxes, the observed trace element distributions suggest that FS is the most important gateway for Arctic‐Atlantic dissolved micronutrient exchange as a consequence of Intermediate and Deep Water transport. Combining fluxes from FS and the Barents Sea Opening with estimates for Davis Strait (GN02, 2015) suggests an annual net southward flux of 2.7 ± 2.4 Gg·a −1 dFe, 0.3 ± 0.3 Gg·a −1 dCo, 15.0 ± 12.5 Gg·a −1 dNi and 14.2 ± 6.9 Gg·a −1 dCu from the Arctic toward the North Atlantic Ocean. Arctic‐Atlantic exchange of dMn and dZn were more balanced, with a net southbound flux of 2.8 ± 4.7 Gg·a −1 dMn and a net northbound flux of 3.0 ± 7.3 Gg·a −1 dZn. Our results suggest that ongoing changes to shelf inputs and sea ice dynamics in the Arctic, especially in Siberian shelf regions, affect micronutrient availability in FS and the high latitude North Atlantic Ocean. Plain Language Summary: Recent studies have proposed that the Arctic Ocean is a source of micronutrients such as dissolved iron (dFe), manganese (dMn), cobalt (dCo), nickel (dNi), copper (dCu) and zinc (dZn) to the North Atlantic Ocean. However, data at the Arctic Ocean gateways including Fram Strait and the Barents Sea Opening have been missing to date and so the extent of Arctic micronutrient transport toward the Atlantic Ocean remains unquantified. Here, we show that Fram Strait is the most important gateway for Arctic‐Atlantic micronutrient exchange which is a result of deep water transport at depths >500 m. Combined with a flux estimate for Davis Strait, this study suggests that the Arctic Ocean is a net source of dFe, dNi and dCu, and possibly also dCo, toward the North Atlantic Ocean. Arctic‐Atlantic dMn and dZn exchange seems more balanced. Properties in the East Greenland Current showed substantial similarities to observations in the upstream Central Arctic Ocean, indicating that Fram Strait may export micronutrients from Siberian riverine discharge and shelf sediments >3, 000 km away. Increasing Arctic river discharge, permafrost thaw and coastal erosion, all consequences of ongoing climate change, may therefore alter future Arctic Ocean micronutrient transport to the North Atlantic Ocean. Key Points: Fram Strait is the major gateway for Arctic‐Atlantic exchange of the dissolved micronutrients Fe, Mn, Co, Ni, Cu and Zn The Arctic is a net source of dissolved Fe, Co, Ni and Cu to the Nordic Seas and toward the North Atlantic; Mn and Zn exchange are balanced Waters of the Central Arctic Ocean, including the Transpolar Drift, are the main drivers of gross Arctic micronutrient export